Melancholia in later life: late and early onset differences in presentation, course, and dementia risk. (12th February 2014) - Sachs‐Ericsson, Natalie; Moxley, Jerad H.; Corsentino, Elizabeth; Rushing, Nicole Collins; Sheffler, Julia; Selby, Edward A.; Gotlib, Ian; Steffens, David C.
<x xml:space="preserve">Abstract</x> Objectives Depression is a risk factor for cognitive decline and dementia. This risk may vary with age of onset and depression subtype. Late onset depression (LOD, 60 years and older) is associated with more cognitive decline, whereas early onset depression (EOD, before 60 years) is associated with more residual depressive symptoms. Potential differences may reflect divergent etiologies. These onset differences, however, have not been examined in the melancholic subtype of depression in older adults. Methods Data were obtained from the Neurocognitive Outcomes of Depression in the Elderly study. Participants (N = 284, 73% EOD–melancholic (EOD‐M) and 27% LOD–melancholic (LOD‐M)) were followed up over 3 years. Factor analyses examined differences in baseline depressive symptoms. Hierarchical linear growth curve models examined changes in depressive symptoms (Montgomery–Asberg Depression Rating Scale) and cognition (mini mental state examination). An annual clinical review panel assigned diagnoses of dementia. Results The LOD‐M participants had more vegetative symptoms at baseline. LOD‐M exhibited greater cognitive decline but fewer residual depressive symptoms than EOD‐M. Among participants who remained in the study for at least 1 year, in uncontrolled analyses, a greater percentage of LOD‐M compared with EOD‐M developed dementia (23.0% vs. 7.8%). Whereas in logistic analyses, controlling for baseline demographics, age at onset remained a predictor of dementia, the odds ratio suggested that the effect was relatively small. Conclusions The EOD‐M and LOD‐M participants have a different presentation and course. LOD‐M may represent a syndrome of neuropsychiatric deterioration with expression of both depressive symptoms and cognitive decline. Copyright © 2014 John Wiley & Sons, Ltd.